2004
DOI: 10.1097/01.prs.0000111593.96440.30
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Postnatal Craniosynostosis and Increased Intracranial Pressure

Abstract: Since its first description by Virchow in 1851, craniosynostosis has been known as a potentially serious condition resulting in premature fusion of skull sutures. Traditionally, craniosynostosis has been regarded as an event that occurs early in fetal development, resulting in a skull shape at birth that is determined by the suture or sutures involved. In recent years, a different form of craniosynostosis has been observed. Patients initially come to the attention of physicians because they exhibit midface hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 10 publications
5
71
0
2
Order By: Relevance
“…Moreover, it turns out that a deflecting growth curve (OFC not changing or showing growth of < 0.5 SD within 2 years) is a very important risk factor for developing papilledema, which is an indirect sign of increased ICP. 9,28,31 A limitation of our study includes its retrospective design. The OFC was often not measured on the day that the CT scan was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it turns out that a deflecting growth curve (OFC not changing or showing growth of < 0.5 SD within 2 years) is a very important risk factor for developing papilledema, which is an indirect sign of increased ICP. 9,28,31 A limitation of our study includes its retrospective design. The OFC was often not measured on the day that the CT scan was performed.…”
Section: Discussionmentioning
confidence: 99%
“…2 All of these patients had a syndromic diagnosis, the most common of which was Crouzon syndrome, and the mean age at presentation was 5.8 years: this is 4 years older than what has been reported for infants (1.1 years) with other forms of craniosynostosis. 2 Rogers and colleagues reported a series of 19 patients with PPP who presented at an average age of 32.4 months.…”
Section: Discussionmentioning
confidence: 76%
“…2,7,10,11 The muted effect on calvarial form is attributable to the latent timing of sutural closure, usually occurring in the first 2 years of life. The majority of patients have an associated syndrome-Crouzon syndrome being most common 2,11 -but the characteristic craniofacial features can be subtle and easily overlooked. Moreover, the absence of significant cranial dysmorphology or phenotypic changes in patients with PPP often results in diagnostic delay and a higher incidence of elevated intracranial pressure (ICP) obJect Progressive postnatal pansynostosis (PPP) is a rare form of craniosynostosis that is characterized by a normal head shape, insidious decrease in percentile head circumference, and high rates of elevated intracranial pressure (ICP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14, 16 Connolly, et al, 10 have also suggested that abnormal skull shape can result in increased intracranial pressure and subsequent developmental deficits. From this point of view, the paradoxically increased overgrowth of the head in the study group during the 2nd to 4th weeks might be a compensatory reaction to intracranial volume changes, and the intracranial volumes during the 5th to 7th weeks might reflect decompensated growth.…”
Section: Experimental Skull Remodeling From Soft-helmet Therapymentioning
confidence: 99%